Gut microbiota-derived short-chain fatty acids and depression: deep insight into biological mechanisms and potential applications - Yan Zhang; Jin Liu; Junzhe Cheng; Hongkun Hu; Yumeng Ju; Mi Wang; Bangshan Liu (General Psychiatry)
The gut microbiota is a complex and dynamic ecosystem known as the ‘second brain’. Composing the microbiota-gut-brain axis, the gut microbiota and its metabolites regulate the central nervous system through neural, endocrine and immune pathways to ensure the normal functioning of the organism, tuning individuals’ health and disease status. Short-chain fatty acids (SCFAs), the main bioactive metabolites of the gut microbiota, are involved in several neuropsychiatric disorders, including depression. SCFAs have essential effects on each component of the microbiota-gut-brain axis in depression. In the present review, the roles of major SCFAs (acetate, propionate and butyrate) in the pathophysiology of depression are summarised with respect to chronic cerebral hypoperfusion, neuroinflammation, host epigenome and neuroendocrine alterations. Concluding remarks on the biological mechanisms related to gut microbiota will hopefully address the clinical value of microbiota-related treatments for depression.